Stability of General Newton Functional Equations for Logarithmic Spirals - John Michael Rassias; Soon-Mo Jung (Advances in Difference Equations, 2008)
We investigate the generalized Hyers-Ulam stability of Newton functional equations for logarithmic spirals.